The recent progress of endocrine therapy-induced osteoporosis in estrogen-positive breast cancer therapy - Xu, Jing; Cao, Bo; Li, Chunyu; Li, Guohui (Frontiers in Oncology, 2023)
Breast cancer is a significant global health concern, and the discovery of endocrine therapy has played a crucial role in the treatment of estrogen-positive breast cancer. However, these therapies are often associated with osteoporosis-related adverse events, which increase the risk of fractures in breast cancer patients and can result in limited mobility and reduced quality of life. Previous studies have shown that osteoporosis is essential side effects of the breast cancer therapy, although the exact mechanisms remain mostly unclear. Current clinical treatments, such as bisphosphonates, cause side effects and may impact the therapeutic response to endocrine drugs. In this review, we explore the likelihood of endocrine therapy-induced osteoporosis in estrogen-positive breast cancer therapy and discuss the involved mechanisms as well as the therapeutic potential of drugs and drug combination strategies.